NF‐κB pathway as a molecular target for curcumin in diabetes mellitus treatment: Focusing on oxidative stress and inflammation - Zamanian, Mohammad Yasin; Alsaab, Hashem O.; Golmohammadi, Maryam; Yumashev, Alexey; Jabba, Abeer Mhussan; Abid, Mohammed Kadhem; Joshi, Abhishek; Alawadi, Ahmed Hussien; Jafer, Noor S.; Kianifar, Farzaneh; Obakiro, Samuel Baker (Cell biochemistry and function, 2024)
Diabetes mellitus (DM) is a collection of metabolic disorder that is characterized by chronic hyperglycemia. Recent studies have demonstrated the crucial involvement of oxidative stress (OS) and inflammatory reactions in the development of DM. Curcumin (CUR), a natural compound derived from turmeric, exerts beneficial effects on diabetes mellitus through its interaction with the nuclear factor kappa B (NF‐κB) pathway. Research indicates that CUR targets inflammatory mediators in diabetes, including tumor necrosis factor α (TNF‐α) and interleukin‐6 (IL‐6), by modulating the NF‐κB signaling pathway. By reducing the expression of these inflammatory factors, CUR demonstrates protective effects in DM by improving pancreatic β‐cells function, normalizing inflammatory cytokines, reducing OS and enhancing insulin sensitivity. The findings reveal that CUR administration effectively lowered blood glucose elevation, reinstated diminished serum insulin levels, and enhanced body weight in Streptozotocin ‐induced diabetic rats. CUR exerts its beneficial effects in management of diabetic complications through regulation of signaling pathways, such as calcium–calmodulin (CaM)‐dependent protein kinase II (CaMKII), peroxisome proliferator‐activated receptor gamma (PPAR‐γ), NF‐κB, and transforming growth factor β1 (TGFB1). Moreover, CUR reversed the heightened expression of inflammatory cytokines (TNF‐α, Interleukin‐1 beta (IL‐1β), IL‐6) and chemokines like MCP‐1 in diabetic specimens, vindicating its anti‐inflammatory potency in counteracting hyperglycemia‐induced alterations. CUR diminishes OS, avert structural kidney damage linked to diabetic nephropathy, and suppress NF‐κB activity. Furthermore, CUR exhibited a protective effect against diabetic cardiomyopathy, lung injury, and diabetic gastroparesis. Conclusively, the study posits that CUR could potentially offer therapeutic benefits in relieving diabetic complications through its influence on the NF‐κB pathway. Significance statement This study explores the role of cellular and molecular elements, such as hyperglycemia‐induced oxidative stress, endothelial dysfunction, and the involvement of the NF‐κB pathway in inflammation and immune regulation in the onset of diabetes mellitus. It extensively investigates the potential therapeutic benefits of curcumin (CUR), a bioactive compound known for its antioxidant, anti‐inflammatory, and hypoglycemic properties, in addressing diabetic complications, predominantly via the modulation of the NF‐κB pathway. The study highlights the importance of the NF‐κB pathway as a molecular target for CUR in the treatment of diabetes mellitus, focusing on oxidative stress and inflammation.